American empire : Roosevelt's geographer and the prelude to globalization - Smith, Neil, 1954-2012 (California studies in critical human geography, 2003)
Arguing that American globalism had a very distinct geography and was pieced together as part of a powerful geographical vision, this text explores US global ambition. The story unfolds through an account of the career of Isaiah Bowman, the most famous American geographer of the 20th century.